2020
DOI: 10.1097/olq.0000000000001155
|View full text |Cite
|
Sign up to set email alerts
|

Otosyphilis: A Review of the Literature

Abstract: The number of cases of syphilis has increased in the United States and in many high-income nations. Otosyphilis is a less recognized complication of syphilis that can lead to irreversible sensorineural hearing loss. Different pathophysiological mechanisms have been proposed to explain hearing loss in otosyphilis. We review the literature on otosyphilis in adults and propose the need for future work in this field to identify better ways to diagnose, treat, and manage this disease. Patients with syphilis should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 22 publications
0
43
0
11
Order By: Relevance
“…Otosyphilis is one of the complications of syphilis that may lead to deafness and other complications if untreated [4]. Otosyphilis can occur at any stage of syphilis [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otosyphilis is one of the complications of syphilis that may lead to deafness and other complications if untreated [4]. Otosyphilis can occur at any stage of syphilis [7].…”
Section: Discussionmentioning
confidence: 99%
“…Despite available preventive and therapeutic strategies, more advanced disease forms occur [3]. Otosyphilis can occur at any stage of the disease, and it is suggested that patients with syphilis be routinely evaluated for otologic symptoms [4]. If not diagnosed early, otosyphilis may cause irreversible hearing loss and further progression of the disease [5].…”
Section: Introductionmentioning
confidence: 99%
“…46 Otosyphilis, or hearing loss due to syphilis, is an important complication of syphilis, but less is known about it, largely because few studies have systematically addressed the problem in individuals with active syphilis. 7 For example, studies from the 1980s and 1990s defined otosyphilis as reactive serum fluorescent treponemal antibody absorption test and hearing loss of unknown etiology; only 22% of patients who met these criteria actually had otosyphilis. 8…”
Section: Introductionmentioning
confidence: 99%
“…Otosyphilis can manifest with a variety of audiovestibular symptoms (hearing loss is the main one). TP may also affect the eighth cranial nerve, the cochleovestibular apparatus, or the temporal bone [30].…”
mentioning
confidence: 99%
“…Otosyphilis can manifest with a variety of audiovestibular symptoms (hearing loss is the main one). TP may also affect the eighth cranial nerve, the cochleovestibular apparatus, or the temporal bone [30].  Early latent syphilis refers to the asymptomatic period between primary and secondary or late syphilis.…”
mentioning
confidence: 99%